Analisis Motivasi Kerja Perawat di Ruang Rawat Inap RS PKU Muhammadiyah Yogyakarta Unit II - Imram Radne Rimba Putri; Elsye Maria Rosa (Alma Ata University Press, 2015)
In hospital, the nurses not only give their service to patients, but they also expect the attention of the management of the hospital where she worked to motivate their work, in order to create optimal performance. This research employed a mixed method research with sequential explanory strategy model. Primary data were collected through in depth interview and used questionnaires. The population is all nurses in PKU Muhammadiyah hospital of Yogyakarta unit II, the sample is 51 nurses to answer the questionnaires and 4 nurses as the informants for the interview since July 2014. The purpose of this study was to analyze the motivation of nurses were reviewed by three dimensions according to the needs of Alderfer’s ERG theory of motivation. The results showed that the majority of nurses work motivation level was as high as many as 49 nurses with a percentage 96.00% and 2 nurses with a percentage 4.00% of nurses with low motivation levels. In descriptive terms of work motivation nurses were categorized high in ERG theory. The conclusion was that the level of motivation of the cnurses the inpatient at ward PKU Muhammadiyah hospital of Yogyakarta unit II analyzed by three dimensional according to the needs of Alderfer’s ERG theory of motivation is high.